2001
DOI: 10.1128/iai.69.6.4027-4033.2001
|View full text |Cite
|
Sign up to set email alerts
|

EspG, a Novel Type III System-Secreted Protein from Enteropathogenic Escherichia coli with Similarities to VirA of Shigella flexneri

Abstract: The function of the rorf2 gene located on the locus of enterocyte effacement (LEE) pathogenicity island of enteropathogenic Escherichia coli (EPEC) has not been described. We report that rorf2 encodes a novel protein, named EspG, which is secreted by the type III secretory system and which is translocated into host epithelial cells. EspG is homologous with Shigella flexneri protein VirA, and the cloned espG (rorf2) gene can rescue invasion in a Shigella virA mutant, indicating that these proteins are functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
162
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(170 citation statements)
references
References 30 publications
(37 reference statements)
6
162
0
2
Order By: Relevance
“…To date, seven EPEC and EHEC effector molecules have been shown to be injected into the host cell by the TTSS. Five translocated effectors are encoded by LEE: Tir/EspE [35,88], Map [87], EspF [109], EspG [45] and EspH [169]. Two effectors are encoded outside the LEE by lambdoid prophages: Cif [104] and NleA/EspI [62,118].…”
Section: The Locus For Enterocyte Effacementmentioning
confidence: 99%
“…To date, seven EPEC and EHEC effector molecules have been shown to be injected into the host cell by the TTSS. Five translocated effectors are encoded by LEE: Tir/EspE [35,88], Map [87], EspF [109], EspG [45] and EspH [169]. Two effectors are encoded outside the LEE by lambdoid prophages: Cif [104] and NleA/EspI [62,118].…”
Section: The Locus For Enterocyte Effacementmentioning
confidence: 99%
“…The genes that are involved in the formation of the AE lesion are encoded by the locus of enterocyte effacement (LEE) chromosomal pathogenicity island 39 . The LEE region encodes a T3SS 40 , an adhesin 41 and its receptor 42 , and effector proteins [43][44][45][46][47] . The mortality that is associated with EHEC infections stems from the production and release of potent Shiga toxin.…”
Section: Ehec As a Case Study: Lessons From A Hijackermentioning
confidence: 99%
“…Three additional proteins, EspA, EspB and EspD, are required for protein translocation into host cells but not for secretion . Five EPEC effectors were identified that are translocated by TTSS into the host cell: Tir (EspE), EspB, EspF, EspG and Map Deibel et al, 1998;Wolff et al, 1998;Kenny and Jepson, 2000;Crane et al, 2001;Elliott et al, 2001;McNamara et al, 2001). Map appears to interfere with the mitochondria membrane potential (Kenny and Jepson, 2000).…”
mentioning
confidence: 99%
“…EspF has been implicated in the disruption of tight junction structure and in the induction of apoptosis (Crane et al, 2001;McNamara et al, 2001). No apparent phenotype was identified in espG knock-out (Elliott et al, 2001). In addition to the local assembly of actin pedestals, EPEC exerts more global effects on the host cell cytoskeleton.…”
mentioning
confidence: 99%